2006
DOI: 10.1097/01.ccm.0000229887.70579.29
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of alkaline phosphatase in septic shock

Abstract: In this clinically relevant septic shock model, alkaline phosphatase administration improved gas exchange, decreased interleukin-6 concentrations, and prolonged survival time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 25 publications
3
54
1
Order By: Relevance
“…A loading dose of BiAP followed by continuous infusion resulted in relatively stable serum enzyme activity in healthy volunteers, pre-exposed to LPS, as well as in sepsis patients, at a level that is approximately double that of endogenous enzyme for a period of 24-72 hours. This was the basis for developing the infusion scheme as reported, and is in concordance with animal data that described a 2-to 4-fold increase in systemic AP levels in septic sheep treated with BiAP, which was associated with prolonged survival time and decreased circulating interleukin-6 levels compared with untreated sheep (Su et al, 2006). Being a nonsialylated glycoprotein, BiAP is primarily cleared by the asialoglycoprotein receptor on liver cells; therefore, a loading dose is required to saturate the liver clearance before a steady state of 2-fold higher AP levels than endogenous circulating levels can be reached and maintained (Beumer et al, 2003).…”
Section: Clinical Trialssupporting
confidence: 83%
See 2 more Smart Citations
“…A loading dose of BiAP followed by continuous infusion resulted in relatively stable serum enzyme activity in healthy volunteers, pre-exposed to LPS, as well as in sepsis patients, at a level that is approximately double that of endogenous enzyme for a period of 24-72 hours. This was the basis for developing the infusion scheme as reported, and is in concordance with animal data that described a 2-to 4-fold increase in systemic AP levels in septic sheep treated with BiAP, which was associated with prolonged survival time and decreased circulating interleukin-6 levels compared with untreated sheep (Su et al, 2006). Being a nonsialylated glycoprotein, BiAP is primarily cleared by the asialoglycoprotein receptor on liver cells; therefore, a loading dose is required to saturate the liver clearance before a steady state of 2-fold higher AP levels than endogenous circulating levels can be reached and maintained (Beumer et al, 2003).…”
Section: Clinical Trialssupporting
confidence: 83%
“…In vivo experiments in mice, rats, and piglets showed a reduction in circulating AP levels during an infection, and subsequent restoration of these levels by BiAP administration suppressed the LPS-induced inflammatory response (Bentala et al, 2002;Beumer et al, 2003). Similarly, BiAP infusion attenuated acute inflammation induced by direct injection of Escherichia coli into the bloodstream, polymicrobial sepsis caused by cecal ligation and puncture in mice, or by intraperitoneal injection of feces into sheep (Verweij et al, 2004;van Veen et al, 2005;Su et al, 2006).…”
Section: Ap Mode Of Action In Sepsis-induced Akimentioning
confidence: 96%
See 1 more Smart Citation
“…AP administration may enhance endogenous dephosphorylating capacity when the need is greatest, such as during acute inflammatory response, to reduce local tissue damage and to retain organ function. Animal models of sepsis have shown exogenous AP to attenuate the inflammatory response and to improve tissue damage and outcomes [16,23] Evaluation of the pharmacokinetics of exogenous AP in humans is complex because the enzyme is also produced endogenously and the activities of endogenous and exogenous enzymes are indistinguishable. We corrected enzyme values for pre-dosing activity, although this does not completely exclude interference from endogenous variations due to circadian and food influences.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by van Veen et al (2005) has shown how cytokine response and neutrophil influx was seen in secondary peritonitis in mice after being attenuated by bovine IAP. Another study by Su et al, (2006) shown that sheep injected with faeces into their peritoneal to create severe peritonitis and septic shock model, have decreased IL-6 concentrations and prolonged survival time after bolus of bovine IAP was administered by intravenous.…”
Section: Alkaline Phosphatase and Lipopolysaccharidesmentioning
confidence: 99%